Thyroid function in hypertensives in South-South Nigeria - Bassey, Iya E.; Gali, Rebecca M.; Essien, Okon E.; Udoh, Alphonsus E.; Emordi, Bukola; Akpan, Uwem O. (International Journal of Research in Medical Sciences, 2016)
Background: Hypertension is the most common cardiovascular disease afflicting humans. It has been reported that hypertensive patients may have a tendency for impaired thyroid function but, these results have not always been confirmed. The aim of this study therefore was to determine the serum level of thyroid hormones in hypertensive subjects and any possible relationship between serum thyroid hormone levels and hypertension. Methods: Blood samples were consecutively obtained from One hundred and seventy (170) consenting subjects. One hundred were hypertensive subjects while seventy subjects were normotensive controls. Triiodothyronine (T3), Thyroxine (T4) and Thyroid stimulating hormone (TSH) were analyzed using ELISA kits. Data was analyzed using student “t” test and analysis of variance. The difference was considered statistically significant at p < 0.05. Results: The mean serum TSH value for hypertensive subjects was 3.01±2.42 µIu/ml and was significantly higher (p<0.0001) than that of the normotensive subjects (1.74±0.92 µIu/ml). Female hypertensive subjects had significantly higher (3.34±2.74 µIu/ml) mean TSH than the female normotensives with mean value of 1.79±0.86 µIu/ml (p<0.002). Mean TSH value for male hypertensive subjects was 2.78±2.4 µIu/ml and was significantly higher (p<0.007) than that of male normotensive subjects (1.72±0.96 µIu/ml). There were no significant differences in the mean serum T3 and T4 levels of hypertensives compared to the normotensives. Conclusions: It is concluded that the hypertensive subjects in this study required significantly higher (p<0.05) stimulation input, as measured from the level of thyroid stimulating hormone, to maintain the same level of thyroid hormones as their normotensive counterparts.